Meta Analysis Study: Person-Organization Fit And Person-Job Fit On Turnover Intention - Karimah Fithri Mardiyah; Dina Sartika (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
The Great Resignation appears as a phenomenon that threatens the company's current existence. This condition was caused by the Covid-19 pandemic which changed work methods to WFH and the shift in the economy towards automation and artificial intelligence. These things motivate employees to resign and increase employee person-job mismatch and job insecurity. Currently, one of the things that drives employees to work is the suitability of employees with company values and culture, also known as PersonOrganization Fit. Previous research has examined the relationship between these three variables, but the conditions in the last five years are far different from before, so this research is intended to examine the effect of PersonOrganization Fit and Person-Job Fit on turnover intention in the last five years. Meta-analysis using JAMOVI software was carried out in analyzing eight selected studies from 51 studies available on Scopus. The results of the study show that both variables have a negative and significant effect on turnover intention. In addition, between the two variables, PersonOrganization Fit has the highest correlation with turnover intention.